FAKTOR PERILAKU DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI DAERAH ENDEMIS KOTA SEMARANG - Dwi Ratna Anggraini; Syamsul Huda; Farid Agushybana (Universitas Muhammadiyah Kudus, 2021)
Introduction: Dengue Hemorrhagic Fever (DHF) is still an important public health problem. DHF is a contagious disease caused by the Dengue virus and transmitted by mosquito vectors from the Aedes aegypti or Aedes albopictus species.Objective: This literature review aims to determine behavioral factors with the incidence of DHF in endemic areas of Semarang CityMethods: The study used in this article is a literature study that examines various references that are closely related to behavioral factors with the incidence of dengue fever with Google Scholar as a source of article searches, at least 2013 articles from national ISSN articles / journals. There were 50 articles identified by Google Scholar and 6 that met the inclusion criteriaResults: The results of the review of the literature that were reviewed, behavioral factors with the incidence of dengue include the behavior of draining the water reservoir 1 time a week, closing the water reservoir, burying used items so that they do not become mosquito nests, sowing abate powder in the water reservoir so that there are no larvae, the habit of disturbing clothes so that they can become mosquito nests in the house, installing gauze at home so that mosquitoes cannot enter, using mosquito repellent lotion, good PHBS and good preventive practicesConclusion: Behavioral factors with dengue fever are the behavior of draining water reservoirs, closing water reservoirs, burying used goods, sowing Abate powder, hanging clothes, putting gauze, wearing mosquito repellent lotions, PHBS and good practices. Keywords: Behavioral factors, incidence of dengue fever